Employing the Dimensions of Psychological Engineering in Enhancing The Core Competencies of Human Resources An Analytical Study of the Opinions of A Sample of Workers in Nineveh Education Directorate (NTU journal for Administrative and Human Sciences (JAHS), 2025)
The current study aims to know the nature of the relationship and the impact of psychological engineering with its dimensions of (sensory awareness, thinking results, behavioral flexibility, familiarity) on the fundamental capabilities of the human resource with its dimensions of (knowledge, skills and situations). The field of study is the General Directorate of Education of Nineveh Governorate, and the study was applied to a (random) sample of (307) individuals working in the administrative departments and divisions of the organization under study. The study relied on the descriptive analytical approach, using the questionnaire as the main tool for collecting data related to the field aspect, in addition to conducting personal interviews, where the main and sub-variables, their connections, influence, and implications were described. The differences between its variables were analyzed to answer questions related to the problem of the study and reach the objective objectives. To process data and information, many statistical methods were used, namely (frequencies, percentages, arithmetic means, standard deviations, and confirmatory factor analysis), by adopting ready-made statistical programs (SPSS.V26) and the package (AMOS.V24). ) To test the study hypotheses and ensure their validity. Based on the results of the statistical analysis, the study reached a number of conclusions, the most important of which is the existence of a correlation and a significant impact at the macro and micro levels of psychological engineering on the fundamental capabilities of the human resource.